PENINGKATAN KESEJAHTERAAN MASYARAKAT MELALUI PEMBERDAYAAN EKONOMI DAN PENDIDIKAN DI DESA LEUWIMALANG - Wibowo, Heru; Zulqarnain, Ahmad Faiz; Harahap, Cindy Yuliana; Amalia, Reza Rossa; Humayra, Aisyah; Firmansyah, Dafidt; Fikri, Hasbiallah Nur; Syabilla, Kais; Sandi, Mahesa; Zikri, Muhammad; Fauziah, Nafra; Rahayu, Qhory Anisa (LPPM Institut Pendidikan Nusantara Global, 2024)
KKS or Social Work Lecture is an activity aimed at serving the community with the goal of developing needy villages. This community service activity includes educational and entrepreneurial development. The activity is carried out by students of FAI UHAMKA as the organizers, and the community as the recipients. The activity is implemented by building cooperation with local village officials and the Student Council (OSIS). Located in Leuwimalang Village, Cisarua, Bogor. This KKS program focuses on the development of Islamic religious education, Arabic language, and Sharia economics..